Examination of the influences of global forest governance arrangements at the domestic level - Eba'a Atyi, R.; Maryudi, A.; McGinley, K.; Cadman, T.; Gulbrandsen, L.; Goehler, D.; Hogl, K.; Humphreys, D.; Kant, S.; Kozak, R.; Levin, K.; McDermott, C.; et al. (IUFRO, 2010)
The ultimate goal of many international and transnational attempts to address global problems is to influence domestic policymaking processes rather than simply to constrain or modify the external behaviour of states. This chapter reviews existing scholarship on the impacts that global forest governance arrangements have had on domestic policymaking processes and decisions. We apply a framework that distinguishes ‘economic globalisation’ – the phenomenon of increasing economic integration from ‘internationalisation’, in which international and transnational pressures influence domestic policymaking (Bernstein and Cashore 2000). We review the effects of four distinct pathways of internationalisation in shaping domestic policies: international rules; international norms and discourse; markets; and direct access to domestic policy processes. This framework overcomes longstanding debates about whether globalisation forces a ‘ratcheting down’ of domestic standards in a ‘race to the bottom’, or whether increasing economic and political interdependence can create a ‘race to the top’. The application of the framework to cases in Southeast Asia, Latin America, Africa, Europe and North America reveals that economic globalisation is not determinative. Rather, it interacts with other factors (operating internationally, transnationally and/or domestically) that condition its effects. Key lessons emerge from this review on the conditions under which, and interventions through which, the international forest regime has affected domestic forest policies, as well as on the interventions that might be nurtured to influence and nurture future policy development.